Legal Study on the Establishment of Ibtidaiyah Madrasah (Mi) Ar-Ridho, Tanjung Mulia Village, Kampung Rakyat District, Labuhan Batu Selatan Regency Based on Law No 28 Year 2004 Concerning Amendment to Law Number 16 Year 2001 Concerning Foundations - Muhammad Muiz Hariansyah Hasibuan; Bernat Panjaitan; Nimrot Siahaan; Risdalina Risdalina (Budapest International Research and Critics University, 2022)
This research was conducted to find out about the establishment of Madrasah Ibtidaiyah Ar-ridho, Tanjung Mulia Village, Sub-District of Kampung Rakyat, South Labuhanbatu Regency based on Law No. 28 of 2004 concerning Amendments to Law No. 16 of 2021 concerning Foundations. This research method The research method used by the author is an empirical normative research method, where this research uses the incorporation of normative legal elements and is then supported by adding data from field research. The approach taken by the author is an empirical juridical approach, namely an approach taken by looking at the reality that exists in practice in the field. This approach is also known as a sociological approach which is carried out directly in the field. This research was conducted on Protocol No. 01 Dusun Rantau Kapal Tanjung Mulia Village, Kampung Rakyat District, South Labuhanbatu Regency. This research was reviewed based on compliance with the Regulation of the Minister of Religion of the Republic of Indonesia Number 14 of 2014 concerning the Establishment of Madrasas organized by the Government and Madrasah Penegrian Organized by the Community.